The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1093/ndt/13.4.930
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal IgA glycosylation in Henoch-Schonlein purpura restricted to patients with clinical nephritis

Abstract: These data indicate that the abnormality of IgA1 O-glycosylation seen in IgA nephropathy is also found in Henoch-Schönlein purpura, but only in those subjects with renal involvement, while IgA1 O-glycosylation is normal in patients with other forms of renal disease. These findings lend strong support to a role for altered IgA1 O-glycosylation in the pathogenesis of IgA-associated glomerular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 1 publication
9
108
0
6
Order By: Relevance
“…It has been demonstrated that serum IgA1 display an abnormal O-glycosylation in patients with IgA-N (35-37) or HSP (38 -41) and that this abnormal glycosylation is also found in IgA deposits on mesangial cells (42). Moreover, it has been shown that abnormal IgA glycosylation is restricted to HSP patients with nephritis while it was not observed in HSP patients without nephritis (39). In addition, it has recently been shown that abnormally glycosylated IgA isolated from IgA-N patients significantly increased the apoptotic rate and nitric oxide synthesis activity of cultured mesangial cells, in comparison with IgA fractions isolated from controls (43).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that serum IgA1 display an abnormal O-glycosylation in patients with IgA-N (35-37) or HSP (38 -41) and that this abnormal glycosylation is also found in IgA deposits on mesangial cells (42). Moreover, it has been shown that abnormal IgA glycosylation is restricted to HSP patients with nephritis while it was not observed in HSP patients without nephritis (39). In addition, it has recently been shown that abnormally glycosylated IgA isolated from IgA-N patients significantly increased the apoptotic rate and nitric oxide synthesis activity of cultured mesangial cells, in comparison with IgA fractions isolated from controls (43).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between galactose deficiency and nephritis has been observed in other diseases. Galactose-deficient IgA1 (46) and IgA-IgG circulating complexes (47) are found in sera of patients with HenochSchöenlein purpura who develop nephritis but not in sera of patients who do not. Also, patients with IgA1 myeloma may have very high levels of circulatory IgA1, but only those with aberrantly glycosylated IgA1 develop an immune-complex glomerulonephritis (48,49).…”
Section: Igan -A Disease Of Aberrant Glycosylationmentioning
confidence: 96%
“…The lack of terminal ␤1-galactosyl residues in the hinge region of IgA1 observed in both diseases might be due to a reduced activity of the ␤1,3-galactosyltransferase in peripheral B cells (26 -28). This abnormality is present only in HSP complicated by nephritis, which suggests a pathophysiological role (26). N-Acetylgalactosamine (GalNac) residues exposed on IgA1 because of the lack of terminal ␤1 galactosylation constitute a novel antigen inducing a humoral auto-immune response (29).…”
Section: Iga Abnormalitiesmentioning
confidence: 99%